ANALYSIS OF THE EFFECT INDUSTRIAL EXISTENCE ON THE ENVIRONMENT AND SOCIO-ECONOMY IN INDONESIA - Imron, Mohamad; Pujiati, Amin (Efficient: Indonesian Journal of Development Economics, 2020)
The purpose of this study is to analyze the influence of industry on the water quality index, air quality index, land cover quality index, population health complaints, and gross domestic product. This study uses quantitative methods with panel data, which is a combination of cross section data from 30 provinces in Indonesia and time series for the period 2013-2017. The analytical method used is structural equation model-partial least squares. The results showed that the industry had a significant negative effect on the water quality index, air quality index, and land cover quality index. While the industry has a significant positive effect on population health complaints and gross domestic product. The conclusion from this study is that the industry is more likely to have a negative impact on the environment and social, while the positive impact is more likely to affect the economy. Advice for the government is the need for industrial development efforts accompanied by improvements in environmental quality to maintain system balance.   Tujuan dari penelitian ini adalah untuk menganalisis pengaruh industri terhadap indeks kualitas air, indeks kualitas udara, indeks kualitas tutupan lahan, keluhan kesehatan penduduk, dan produk domestik bruto. Penelitian ini menggunakan metode kuantitatif dengan data panel, yang merupakan kombinasi data cross section dari 30 provinsi di Indonesia dan deret waktu untuk periode 2013-2017. Metode analisis yang digunakan adalah model persamaan struktural-partial least square. Hasil penelitian menunjukkan bahwa industri memiliki pengaruh negatif yang signifikan terhadap indeks kualitas air, indeks kualitas udara, dan indeks kualitas tutupan lahan. Sementara industri memiliki efek positif yang signifikan terhadap keluhan kesehatan penduduk dan produk domestik bruto. Kesimpulan dari penelitian ini adalah bahwa industri lebih cenderung memiliki dampak negatif terhadap lingkungan dan sosial, sedangkan dampak positif lebih cenderung mempengaruhi perekonomian. Saran bagi pemerintah adalah perlunya upaya pengembangan industri disertai dengan peningkatan kualitas lingkungan untuk menjaga keseimbangan sistem.